The Role of Legal Advocacy in Controlling Non-Prescription Antibiotic Use in Indonesia - Muhammad Adymas Hikal Fikri; Aprila Niravita; Indah Zunita Sari; Altares Ainun Qadisah; Berdibek Tursunov; Elsa Ratna Duhita (Universitas Negeri Semarang, 2025)
The provision of antibiotics without doctor's prescription is serious problem in the Indonesian health system, which has impact on increasing antimicrobial resistance (AMR). Although regulations related to antibiotic use have been implemented, there are still gaps between the rules and implementation in the field. This study uses empirical legal method to analyze the effectiveness of controlling the use of antibiotics without doctor's prescription, challenges in its supervision, and strategies that can be applied to limit this practice. The results of the study show that although various regulations have strictly regulated the distribution of antibiotics, the level of pharmacy compliance with these rules is still low. A study conducted by the Indonesian Pharmacists Association (IAI) in 2023 showed that 79.5% of pharmacies still serve the purchase of antibiotics without a prescription, with a dominance in urban areas (82.3%) compared to rural areas (71.8%). The main factors causing this violation are weak supervision, legal sanctions that are not sufficiently deterrent, and high demand from the community. In addition, the lack of health education contributes to misuse of antibiotics, which risks increasing bacterial resistance and economic burden on the health system. Strengthening supervision and law enforcement of antibiotic distribution, implementing an electronic system for recording prescriptions, and educational campaigns for community and pharmacists are needed. With a stricter and more synergistic control strategy, practice of prescribing antibiotics without prescription can be minimized, so that the risk of antimicrobial resistance can be suppressed and effectiveness of treatment can be maintained.